2018
DOI: 10.1016/j.bjhh.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in children, adolescents and adults with sickle cell anemia in Rio de Janeiro, Brazil

Abstract: ObjectiveTo determine the mortality rate of children, adolescents and adults with sickle cell anemia in Rio de Janeiro, Brazil.MethodsThe number of deaths, the mortality rate and the causes of deaths in patients with sickle cell anemia who were treated and followed up at our institution for 15 years were determined and compared to data available for the Brazilian population.ResultsThe overall number of deaths was 281 patients with a mortality rate of 16.77%. Survival probability was significantly higher in fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 21 publications
6
48
0
7
Order By: Relevance
“…Regarding gender, the higher mortality rate observed for males resembles data obtained in other studies, 38,39 although several studies have also found a higher mortality rate among women, especially in the adult period, which reinforces the non-relationship between the SCD and the gender of the individuals.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding gender, the higher mortality rate observed for males resembles data obtained in other studies, 38,39 although several studies have also found a higher mortality rate among women, especially in the adult period, which reinforces the non-relationship between the SCD and the gender of the individuals.…”
Section: Discussionsupporting
confidence: 84%
“…(12) Relatively lower blood viscosity in women, due to low levels of Hb and hematocrit, may be one of the possible causes. (9) The median age of participants in the present study was 35 (18-70) for those with HbSS, and 31 (18-82) for HbSC patients; there was no association between age and genotype. These results are similar to those found in a study of 132 African-American individuals, whose participants ranged in age from 15 -70 years, with a mean age of 34.2 years.…”
Section: Discussionmentioning
confidence: 45%
“…(7,24) However, regular treatment, adherence to treatment, family support, and lifestyle are important for reducing morbidity and mortality. (9) In the state of MS, human and technological resources are concentrated in the municipalities of Campo Grande and Dourados, revealing a low resolution for the treatment of hemoglobinopathies in health microregions. The access to the hematologist in the public network depends on the agreement of the municipality of origin of the patient with the capital, ordered by a state central of regulation, which can generate a repressed demand for consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCD crises can initially present in a very similar way to a joint bleed and are very painful, but it is not clear how best to help patients distinguish between the two to allow prompt treatment. Monthly blood transfusions have improved quality of life for children with SCD and have increased longevity, so that survival into old age is now the expectation for many, at least in wealthier economies [10,11] . However, this means they look forward to a future marred by organ damage and debility due to complications [1,2] .…”
Section: The Outlookmentioning
confidence: 99%